Cost-Quality Tradeoffs in Cream Cheese Formulation: Evaluating Acidulants for Sensory Performance and Financial Sustainability - Wahyuningtyas, Amalina Nur; Nurmasytha, Andi (FORUM EKONOMI: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This study assesses the physicochemical, sensory, and economical aspects of cream cheese production utilizing five different acidulants (citric acid, vinegar, lemon juice, papaya latex, and orange juice) in order to discover the most commercially viable compositions. Sensory analysis revealed that orange juice and citric acid produced the most preferred products, with bright white color, balanced sourness, and ideal firmness, whereas papaya latex produced inferior results due to excessive softness and weak flavor caused by its higher pH (5.57). Financial analysis yielded key insights into production economics, with a break-even threshold of 909 units/month (IDR 31.8 million in sales) and a small 9.1% margin of safety at 1,000 units. The cost structure revealed variable expenses (IDR 24,000/unit) dominated by raw materials (75%), emphasising the need of strategic acidulant selection for profitability. The findings show that, while orange juice and citric acid have better sensory properties, their commercial viability is dependent on cost-effective procurement to sustain goal margins. In contrast, the enzymatic benefits of papaya latex were outweighed by low consumer acceptance, rendering it financially unviable despite possible cost reductions. The study concludes that successful cream cheese production necessitates formulas that balance sensory perfection with economic sustainability, especially given the tight profit margins and volume sensitivity. These findings offer dairy producers meaningful insights for improving both product quality and financial success. Future study should look into hybrid acidulant systems or process improvements to increase the cost-effectiveness of high-performing formulations while keeping favorable sensory properties